ANALISIS PENYERAPAN TENAGA KERJA DI SEKTOR KULINER KABUPATEN BIREUEN - Zarimah, Zarimah; Haryani, Haryani (Fakultas Ekonomi Universitas Almuslim Bireuen, 2023)
The purpose of this research is to analyze how wage levels and production values influence the absorption of labor in the culinary sector of Bireuen district. The type of research used in this research is quantitative research. In this study, the population is the culinary sector in Bireuen district by taking 49 culinary samples as respondents. Data collection techniques through questionnaires. Statistical tools used via multiple linear regression. Based on the SPSS calculation results, it shows that partially the wage rate variable (x1) has a positive and significant effect on employment absorption and the production value variable (x2) has a positive and significant effect on employment absorption. Then simultaneously the wage rate (x1) and production value (x2) have an influence on employment.